Tarot : Interpretation and Divination - Dee, Jonathan, 1957-2010 (Worcestershire King Books, 2012)
The complete guide to understanding Tarot cards and how to interpret their symbolism. Includes the origins ands history of cards, and how Tarot compares to and complements other methods of divination.
Include Illustrations and Index
Keywords: Tarot cards